Evaluation methods of mechanical properties for low-k dielectrics - I. S. Ovchinnikov (Российский технологический журнал)
This review introduces the study of state-of-art methods for assessing the mechanical properties of insulating materials with low dielectric constant. The main features of measuring Young’s modulus of thin films insulating materials with low dielectric constant are determined by usage of Brillouin light scattering, surface acoustic wave spectroscopy, picosecond laser-acoustic method, ellipsometric porosimetry, nanoindentation and atomic force microscopy in various modes. The author estimated the optimum lateral and optimum depth resolution for each above method. The review analyzes the degree of sample preparation complexity for the measurements by these methods and describes what methods of measurement are destructive for the samples. Besides, the review makes a comparison for the results of evaluating Young’s modulus of insulating materials with low dielectric constant achieved by different methods. Comparative analysis of the methods for assessing mechanical properties lead us to the conclusion that the method of atomic force microscopy is superior to other methods described above, both in lateral (8 nm) and optimum depth (10 nm) resolution. It is shown that due to the small impact force of the atomic force microscope probe on the surface, the method does not have a destructive effect on the sample. In addition, there is no need to create special conditions for the experiment (e.g., the cleanliness level of the premises, the possibility of an experiment under environmental conditions, etc.). This makes the experiment relatively simple in terms of preparing the object of research. It has been also established that the method of atomic force microscopy in the mode of quantitative nanomechanical mapping allows forming a map of the distribution of the Young’s modulus of the insulating material as part of the metallization system of integrated circuits.